Architecture Design of Intelligent Assembly System Based on Complex System. (September 2020) - Zhang, Dashun; Meng, Fanjun; Wang, Jing; Miao, Liqin; Hu, Huizhong; Li, Penghui; Li, Xueguang
Abstract: For complex system and product, the virtual and intelligent assembly system can short the designing and manufacturing time effectively, especially for administration of life cycle of product, it can provide the digital models for different period using. In this paper, the intelligent assembly system architecture was designed which includes three-layers, application layer, data layer, and output layer. By using this intelligent assembly system the virtual assembly of complex system products is realized. Then, the framework of intelligent assembly information modelling was designed further which includes geometric information, assembly constraint information, and assembly relationship information. This assembly information model can not only express the connection between assembly parts and assembly relationships, but also provide information sources and acquisition mechanisms for assembly process planning. At last, an example of product assembly is presented which includes 3D models analysis and attribute set for simulation, the intelligent assembly function is accomplished in the end.